Tingkat Kenakalan Remaja dalam Kaitannya dengan Perkembangan Teknologi - Hakim, Abd. (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2023)
An important element of living in community is the ability to manage emotions well. Goleman's research shows that only about 20% of the remaining 80% of IQ success is determined by a related factor called emotional intelligence. In fact, today we see that a high IQ does not necessarily mean success or a happy life. People with high IQ but are emotionally unstable and angry often cannot identify and solve problems in life due to their inability to concentrate. Emotions do not develop, do not become overwhelming, often make changes when faced with problems and treat others with too much conflict. Emotions are less processed, easily controlled by others, sometimes enthusiastically agree to something but in a short time turn to refusal, which hinders the agreed cooperation with others other. In Islamic education, people pay great attention to this issue. The mission of Islamic education is to guide and direct the growth and human development of students from one stage of life to another to achieve optimal achievement scores. Pay attention to Islamic education in terms of IQ and EI, because Islamic education has a great impact on the development of education, knowledge and intelligence.